The prevalence of metabolic syndrome is increased in patients with anti-neutrophil cytoplasmic antibody-associated vasculitis - Atas, Dilek Barutcu; Atas, Halil; İzgi, Tuba Nur; Velioglu, Arzu; Arikan, Hakki; Oner, Fatma Alibaz; Direskeneli, Haner; Tuglular, Serhan; Asicioglu, Ebru (International urology and nephrology, 2021)
Purpose Cardiovascular disease is one of the major causes of mortality in anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV). Metabolic syndrome (MetS) is associated with increased cardiovascular risk in the normal population. However, MetS in AAV has not been adequately investigated. We aimed to determine MetS prevalence and associated factors in AAV patients. Methods Thirty-seven AAV patients and 42 healthy controls were enrolled. MetS was determined by International Diabetes Federation (IDF) and National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATPIII) criteria. The relationship between clinical features of AAV and MetS was also investigated. Results MetS was significantly higher in AAV patients than controls by NCEP-ATPIII (51.4% vs. 26.2%, p 0.022) and IDF (62.2% vs. 35.7%, p 0.020). When AAV patients with MetS were compared to those without, there were significant differences in age, CRP, GFR and NT-pro-BNP. Age [58 (13) vs. 50 (8) years p: 0.028], CRP [4.0 (3.6) vs. 3.2 (1.0) mg/l, p 0.021] and NT-pro-BNP [173.5 (343.7) vs. 106.0 (103.0) pg/ml, p 0.013] were significantly higher in AAV patients with MetS than those without; GFR was significantly lower [38 (46) vs. 83 (51) ml/min/1.73 m 2 , p 0.004]. ROC curve analysis showed NT-pro-BNP > 58.0 ng/ml predicted MetS with 87.1% sensitivity and 46.7% specificity (Area under curve: 0.71, CI 0.536–0.902, p 0.041). Multivariate analysis revealed age [OR (95% CI): 1.180 (1.010–1.370), p 0.039] and NT-pro-BNP > 58 pg/ml [OR (95% CI): 5.5 (1.02–30.1) p 0.047] were independent predictors of MetS in AAV patients. Conclusion MetS is significantly higher in AAV patients than controls and is associated with age and NT-pro-BNP. Screening and treating MetS may improve prognosis in AAV patients.